Serum Level of Ligand Programmed Death-1 in Endometriosis - Akhmaltdinova, Lyudmila; Appazova, Leila; Turdybekova, Yasminur; Kopobayeva, Irina; Amirbekova, Zhanna; Marinkin, Igor (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: In this study, is to evaluate serum level of ligand programmed death-1 (PDL1) in patients with genital endometriosis. MATERIAL AND METHODS: For PDL-1, cancer antigen 125 (CA 125), interleukin (IL)-6, IL-8, tumor necrosis factor (TNF), and vascular endothelial growth factor (VEGF) determination, venous blood was taken 1 h before surgery and/or treatment. All patients were stratified by the presence or absence of endometriosis according to the American Society of Reproductive Medicine’s Revised Classification of Endometriosis of the American Society of Reproductive Medicine. RESULTS: Twenty-one patients with endometriosis participated in the study. The PDL-1 level an experienced group was 55.32 ng/ml (interquartile range [IQR] 34.53–76.20); in the control group was 19.72 ng/ml (IQR 14.72–24.78), which was a statistically significant decrease (p < 0.001). A significant increase in CA125 31.87 (IQR 15.43–36.96) was detected (p < 0.001). In the experimental group, all pro-inflammatory cytokines were elevated (IL-6, IL-8, and TNF, p < 0.013; <0.001; and <0.001) and almost twice increased VEGF 243.44 (IQR 194.56–328.07), (p = 0.016). A noticeable correlation was found between the following indicators PDL-1-CA125, PDL-1-IL-8, and PDL-1-TNF, and a moderate correlation was found between PDL-1 and VEFF (p = 0.006). CONCLUSIONS: The results of the study showed that the levels of PDL-1, CA 125, IL-6, IL-8, TNF, and VEGF were statistically significantly different in the experimental and control groups, and a correlation was also revealed between the levels of PDL-1 and CA125, IL-8 and TNF in patients with genital endometriosis. Therefore, further studies with larger numbers of patients are required.